Comparing higher education preferences with labour market needs - Gebei , Tímea; Vincze, Szilvia (International Journal of Engineering and Management Sciences, 2020)
Hungarian institutions of higher education play an important role in national economy: they ensure intellectual labour with appropriate knowledge and professional competencies for Hungary in all profession fields. If the rules of private sector are applied for these institutions – interpreting it within a certain framework as the quality of education and research has to be maintained and there are social benefits associated with them -, they owned by the state, their management is the institutional leadership and their consumer is the labour market. Thus, training programmes must or should be developed in accordance with the needs of labour market. It represents a major challenge, even without taking into consideration other factors, since future requirements should be aimed (at least a 3-5 year training period later) – along with a rapid technological development. Even if the state makes significant efforts to adapt training programmes to meet the requirements of the labour market demands, students who want to further their education pay limited attention to these factors in their educational decision-making. Partly for this reason, career transition or shortages may occur in the case of certain professions. This paper seeks to address to what extent the most popular training programmes meet the expectations and to what extent the degree earned may be regarded as a ‘success’ in the labour market; moreover, if they do not overlap each other, how much applicants prefer those training programmes which are to be considered the most successful based on recruitment information. Admission statistics of Education Department and database of DPR provide the necessary information for the period 2010-2017 and these data sources enable authors to follow-up students from application to higher education until employment.